The Influence of Digital Supply Chain Agility, Digital Cultural Transformation, and Sustainable Innovation on Digital Revenue Resilience in the MSME Sector - Gai, Ardiyanto Maksimilianus; Apramilda, Riesna; Hamdany, Mohammad Azharie; Syofya, Heppi; Yusnanto, Tri; Defitri, Siska Yulia (Yayasan Gema Bina Nusantara, 2026)
Micro small and medium enterprises need to overcome difficulties which diminish their financial success through digital economy benefits which create new business opportunities. The researchers of this study investigate how digital supply chain agility and digital cultural transformation together with continuous innovation impact digital revenue resilience which exists within the MSME sector. The researchers of this study implement their research through a quantitative method which uses an explanatory framework. The research data were obtained by distributing questionnaires to 160 MSME respondents who have adopted digital technology in their business activities using a purposive sampling technique. The researchers used multiple linear regression analysis to examine data after they conducted validity testing and reliability testing together with classical assumption testing. The study shows that digital supply chain agility and digital cultural transformation together with continuous innovation create positive effects which help organizations achieve digital revenue resilience. Digital supply chain agility enhances operational flexibility and product distribution systems because organizations use digital cultural transformation to adopt digital technologies. Continuous innovation enables organizations to develop products and services which better satisfy changing market needs thus improving their business competitiveness. The study results provide business practitioners with guidance which helps them develop digital business strategies that sustain their organizations through changing times.